Gluteal subcutaneous adipose tissue in women of different ages and body mass index observed by magnetic resonance imaging. (28th February 2022) - Hexsel, Doris; Dal'Forno Dini, Taciana; Belem, Luciana; Tanure Correa, Isabella; Brandão, Alice
Abstract: Background: Magnetic resonance imaging (MRI) is a recognized method to assess the morphological characteristics of subcutaneous adipose tissue (SAT). This study aimed to assess objectively different characteristics of SAT of women with different ages and body mass index (BMI) using MRI. Materials and Methods: Retrospective, observational study. Pelvic‐MRI exams of 133 women aged between 15 and 80 years, with BMI 16–30 kg/m 2 were assessed. Results: There was a moderate positive correlation between the total fat thickness and the BMI ( r  = 0.64; p  < 0.0001) considering the entire sample. Within the different age groups, strong positive correlation was observed for age groups 15 to 30 years ( r  = 0.76; p  < 0.0001) and 46 to 60 years ( r  = 0.75; p  < 0.0001), and moderate positive correlation in the others ( r  = 0.61; p  < 0.0001 [31–45 years] and r  = 0.53; p  < 0.0001 [>61 years‐old]). There was no correlation between age and fat layer thickness. Correlation between deep fat layer thickness and BMI showed similar pattern to that of the total fat layer. Within the different BMI groups, SAT thickness tends to decrease with aging in patients with low BMI. Conclusion: Inside each age group, the average thickness of the total fat layer increases according to BMI. The results suggest that BMI influences the thickness of SAT throughout life and how SAT changes with age in patients with different BMI. In patients with moderate BMI, the thickness of SAT remains stable.